Collective Bargaining as a Fundamental Right - Gilberto Stürmer (Revista de Direito Econômico e Socioambiental)
This article has the purpose of analyzing collective bargaining as a fundamental right. This article starts from a conceptual analysis of collective labor conflicts, followed by a study of collective bargaining as a fundamental right, based on the 1988 Federative Republic of Brazil Constitutions, the International Labor Organization conventions ratified by Brazil on the matter and the domestic law on the topic, such as the recently approved Law no. 13,467 dated July 13th 2017, which shall enter into force 120 days after the publication thereof. The new sections 611-A and 611-B of the Consolidation of Labor Laws propose that collective bargaining be legally binding, excluding the cases that are part of the list of fundamental social labor rights set forth in section 7 of the Federal Constitution which cannot be subject to negotiation.